2017
DOI: 10.1002/anie.201708242
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Conformational Variants of Solution‐Phase Intrinsically Disordered Tau Protein at the Single‐Molecule Level

Abstract: Intrinsically disordered proteins, such as tau protein, adopt a variety of conformations in solution, complicating solution-phase structural studies. We employ an anti-Brownian electrokinetic (ABEL) trap to prolong measurements of single tau proteins in solution. Once trapped, we record the fluorescence anisotropy to investigate the diversity of conformations sampled by the single molecules. A distribution of anisotropy values obtained from trapped tau protein is conspicuously bimodal while those obtained by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 48 publications
5
25
0
Order By: Relevance
“…For example, NMR studies have also shown clear evidence of multiple conformations of tau existing in solution, but teasing out the molecular details of these conformers is difficult and indirect 13 . In contrast, solution-phase singlemolecule measurements are powerful methods for characterizing heterogeneous conformations within, and interactions involving, IDPs 11,[14][15][16][17] . Multiple solution-phase Förster resonance energy transfer (FRET) experiments at the single-molecule level have revealed unexpected behaviors of IDPs including simultaneously existing populations which evolve over time 18 or multiple static subpopulations 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, NMR studies have also shown clear evidence of multiple conformations of tau existing in solution, but teasing out the molecular details of these conformers is difficult and indirect 13 . In contrast, solution-phase singlemolecule measurements are powerful methods for characterizing heterogeneous conformations within, and interactions involving, IDPs 11,[14][15][16][17] . Multiple solution-phase Förster resonance energy transfer (FRET) experiments at the single-molecule level have revealed unexpected behaviors of IDPs including simultaneously existing populations which evolve over time 18 or multiple static subpopulations 19 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study using steady-state fluorescence anisotropy of tau protein in an ABEL trap showed that the full-length isoform of tau (htau40) has at least two stable families of conformations with differences in protein compaction which can be resolved by steady-state anisotropy 17 . However, steady-state anisotropy measurements are unable to determine the different rotational parameters that define that compaction.…”
Section: Introductionmentioning
confidence: 99%
“…This approach allowed the photophysical process in light‐harvesting complex II to be analyzed (Figure a, right; Schlau‐Cohen et al, ). Time‐resolved fluorescence anisotropy measurements in an ABEL trap revealed two distinct conformation families of tau proteins (Manger et al, ), which will give a good insight on understanding the aggregation process in Alzheimer's disease.…”
Section: Emerging Tether‐free Single‐molecule Approachesmentioning
confidence: 99%
“…By doping in a small amount of tracer uorophore, the rotational dynamics of the tracer molecule can be used to report on the chemical evolution of its environment. Measurements of uorophore rotational dynamics via uorescence anisotropy have been used to investigate a broad variety of polymeric systems, including measuring the mobility of graed polymer chains in microgels, 63 observing the movement of small molecules in crosslinked polystyrene networks, 64 following production of silica gels, 65 photocuring of polymers, 66 studying the selfassembly of block copolymers in water, 67 quantifying distributions of conformers of intrinsically disordered proteins in solution, 68,69 and studying dynamics within supported polymer thin lms and glasses. 70 There are very few studies that employ uorescence polarization anisotropy measurements in droplets.…”
Section: Introductionmentioning
confidence: 99%